Transformative learning within Australian Indigenous studies: a scoping review of non-Indigenous student experiences in tertiary Indigenous studies education. Issue 1 (2nd January 2021) - Bullen, Jonathan; Roberts, Lynne D.
ABSTRACT: Transformative learning theory is widely considered one of the pre-eminent theories of adult education, and has been adopted as a means of developing and understanding adult learning across a range of disciplines. While the representation and conceptualisation of transformative learning experiences has grown within Australian Indigenous studies curriculum contexts, significant differences are apparent in the means of engagement with Mezirow's theoretical framework. This article adopts Arksey and O'Malley's scoping review methodology to establish what is known about non-Indigenous student transformative learning within the Australian Indigenous studies literature, and provide recommendations for future research that can inform the use of Mezirow's theory within Indigenous Australian studies curricular contexts. Four databases were systematically searched for papers focusing on transformative learning experiences of non-Indigenous students within Australian tertiary Indigenous Studies contexts, with 17 papers published between 1978 and 2019 included in the final analysis. While findings suggest the fundamental building blocks of Mezirow's theory are quite well understood, they also highlight gaps in the literature. First, questions remain around the enduring effects of transformative learning outcomes. Second, associations between transformative learning theory and cultural capability development appear to lack clarity. Third, associations between transformative learning and Indigenous health outcomes are unclear. Finally, there is a need for more diverse paradigms, methods and methodologies within transformative learning research.